Occurrence of Diodon eydouxii (Actinopterygii: Diodontidae), in the Azores and comparison with Pacific specimens - Barreiros, João P. (2015)
A specimen of porcupine fish was collected by a fisherman at Terceira Island, Azores (north-eastern Atlantic), and identified as the pelagic porcupinefish, Diodon eydouxii Brisout de Barneville, 1846, a species recently recorded for the first time from the Azores. This record, together with an examination of the first reported specimen, allowed us to compare the external morphology with Pacific specimens. The possibility of this species to be relatively common in the Azores is discussed.